Amniotic Constriction Bands: Secondary Deformities and Their Treatments. (May 2019) - Drury, Benjamin T.; Rayan, Ghazi M.
Background: The purpose of this study was to report the surgical treatment experience of patients with amniotic constriction bands (ACB) over a 35-year interval and detail consequential limb deformities with emphasis on hands and upper extremities, along with the nature and frequency of their surgical treatment methods.Methods: Fifty-one patients were identified; 26 were males and 25 females. The total number of deformities was listed. The total number of operations, individual procedures, and operations plus procedures that were done for each patient and their frequency were recorded.Results: The total number of operations was 117, and total number of procedures was 341. More procedures were performed on the upper extremity (85%) than the lower extremity (15%). Including the primary deformity ACB, 16 different hand deformities secondary to ACB were encountered. Sixteen different surgical methods for the upper extremity were utilized; a primary procedure for ACB and secondary reconstructions for all secondary deformities. Average age at the time of the first procedure was 9.3 months. The most common procedures performed, in order of frequency, were excision of ACB plus Z-plasty, release of partial syndactyly, release of fenestrated syndactyly, full-thickness skin grafts, resection of digital bony overgrowth from amputation stumps, and deepening of first and other digital web spaces.Conclusions: Many hand and upper extremity deformities secondary to ACB are encountered. Children with ACB may require more than one operation including multiple procedures. Numerous surgical methods of reconstruction for these children's secondary deformities are necessary in addition to the customary primary procedure of excision of ACB and Z-plasty.